Guanylate binding protein-1 inhibits spreading and migration of endothelial cells through induction of integrin α4 expression - Weinlaender, Kristina; Naschberger, Elisabeth; Lehmann, Michael H.; Tripal, Philipp; Paster, Wolfgang; Stockinger, Hannes; Hohenadl, Christine; Stürzl, Michael (The FASEB Journal, 2008)
Human guanylate binding protein-1 (GBP-1) is a large GTPase that is induced by inflammatory cytokines and acts antiangiogenically through the inhibition of endothelial cell proliferation and migration. In this study, we detected that GBP-1-expressing cells show a significantly reduced spreading and migration on fibronectin matrices. Investigating possible mechanisms of these effects, we found that integrin α4 (ITGA4) was consistently up-regulated at both the RNA and protein level in GBP-1-expressing cell cultures. Inhibition of cell spreading and migration by GBP-1 was dependent on the binding of ITGA4 to fibronectin. The inflammatory cytokines IL-1β and TNF-α induced ITGA4 expression in HUVECs and inhibited spreading and migration. Knockdown of GBP-1 by shRNA abrogated inflammatory cytokine induced ITGA4 expression and restored spreading and migration capabilities of the cells. These results show that inhibition of endothelial cell spreading and migration by inflammatory cytokines is mediated by GBP-1 through induction of ITGA4 expression. Endothelial cell migration is a key process during angiogenesis. Therefore, ITGA4 may be a novel molecular target to modulate angiogenesis in human disease. © FASEB.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Inflammation; Integrins; Large GTPase